2013
DOI: 10.1007/s00253-013-4971-1
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes survival in aging submerged cultures of the filamentous fungus Aspergillus niger

Abstract: Autophagy is a well-conserved catabolic process constitutively active in eukaryotes that is involved in maintaining cellular homeostasis by the targeting of cytoplasmic content and organelles to vacuoles. Autophagy is strongly induced by the limitation of nutrients including carbon, nitrogen, and oxygen and is clearly associated with cell death. It has been demonstrated that the accumulation of empty hyphal compartments and cryptic growth in carbon-starved submerged cultures of the filamentous fungus Aspergill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 59 publications
7
54
0
Order By: Relevance
“…29,37 In line with this idea, Foatg8D mutants exhibited reduced aerial hyphae and conidiation, as reported in other filamentous fungi. 5,910,14,28,29 In fungal pathogens, successful infection might depend on the recycling of macromolecules to support cellular activity under nutrient-limiting conditions in the host. We found that virulence of Foatg8D mutants on both tomato plants and G. melonella larvae was significantly attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,37 In line with this idea, Foatg8D mutants exhibited reduced aerial hyphae and conidiation, as reported in other filamentous fungi. 5,910,14,28,29 In fungal pathogens, successful infection might depend on the recycling of macromolecules to support cellular activity under nutrient-limiting conditions in the host. We found that virulence of Foatg8D mutants on both tomato plants and G. melonella larvae was significantly attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,10,14,28,29 We therefore determined vegetative growth and conidiation on solid and in liquid media, both in rich and minimal medium. Under highnutrient conditions, colonies of the Foatg8D mutants showed slightly reduced radial growth ( Fig.…”
Section: Autophagy Is Required For Proper Vegetative Growth and Conidmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from nutrient-rich growth conditions to lignocellulose involves a carbon starvation response in A. niger [42]. The carbon starvation response involves the induction of ER-autophagy genes and CAZyme-encoding genes (many of which are predicted to be involved in cell autolysis) [47,146]. Wheat straw also up-regulated the transcript levels of ER-autophagy genes in T. reesei [121].…”
Section: Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
“…The phenomenon contributes to the survival of filamentous fungi under harsh environmental conditions like carbon shortage [3] as its main function is to supply developmental processes with energy sources [4,5].…”
Section: Introductionmentioning
confidence: 99%